Studies on nutritional requirement for aswagandh (Withania somnifera Dunal) in Shevroy hills of Tamil Nadu, India - BALAKRISHNAMURTHY, D MUTHUMANICKAM, G (Journal of Spices and Aromatic Crops, 1999)
Nutritional trials were conducted at Yercaud (Tamil Nadu, India) with the objective of increasing root yield and to determine the optimum nutrition level in aswagandh (Withania somnifera). The results indicated that a dose of 40,60,20 kg N, P2O5 and K2O/ ha (entire dose of P2O5, K2O and 50% N basal + 50% N top dressing) recorded the highest dry root yield of 770.37 kg ha-1. There was also improvement in the length of roots, number of root primaries and total withanolides content due to the nutrient application.